Comparison of major carbon offset standards for soil carbon projects in Australian grazing lands - Kalpana Pudasaini; John Rolfe; Thakur Bhattarai; Kerry Walsh (Carbon Management)
Despite the potential role of soil carbon offset schemes to reduce greenhouse gas emissions, there are concerns that the rules for assessment, monitoring, and operation are barriers to engagement. This may explain why there is low participation of Australian landholders in soil carbon projects. This study reviews the literature on three leading voluntary carbon standards and methods to assess their suitability for developing soil carbon projects in grazing systems in Australia. The soil carbon method of each standard was analysed based on several criteria: scope, eligibility/applicability, newness and additionality, permanency, baselines and quantification methodology, environmental sustainability, safeguard mechanism, and crediting period. A hypothetical grazing case study in Central Queensland, Australia’s premier beef cattle region, was used to model the cost-effectiveness and potential returns from establishing soil carbon projects under the three standards. Results show that credits created under the Emissions Reduction Fund in Australia generate higher returns for soil carbon projects compared to the Verified Carbon Standard and Gold Standard. This is largely due to a higher market price for soil carbon credits in the Emissions Reduction Fund, reflecting more robust standards of assessment and verification. While assessment costs for credits were higher in the international schemes, returns were lower because prices reflected less rigorous standards.